(untitled) (Microbes and Health, 2013)
The prevalence of caprine subclinical mastitis in Mymensingh area was assessed by California Mastitis Test (CMT). Milk samples were also analyzed for the isolation and identification of bacterial agents that might be associated with caprine subclinical mastitis including their antibiotic sensitivity pattern against commonly used antibiotics. In addition, the influ-ence of certain risk factors such as age of animal, parity, length of lactation period, type of farming system and type of housing floor, on the prevalence of caprine subclinical mastitis was also evaluated. Milk samples were collected from 59 goats (113 udder halves). The overall prevalence of caprine subclinical mastitis as determined by CMT was 18.64%. On an udder half basis the prevalence was 15.04%. Certain risk factors associated with caprine subclinical mastitis were identified. The prevalence was higher in older animals, with greater parity and longer lactation period. The prevalence was also higher in farms where goats were raised under traditional farming system with earthen floors. The predominant bacterial species isolated from milk that were collected from the subclinical mastitis positive cases were Staphylococcus aureus, S. epidermidis and Bacillus subtilis, that showed various degrees of sensitivity to the antibiotics used in the study. DOI: http://dx.doi.org/10.3329/mh.v1i1.13705 Microbes and Health Vol.1(1) June 2012 pp.1-5